Якість життя та респіраторні порушення у пацієнтів із хронічним обструктивним захворюванням легень та гіпертонічною хворобою: погляд крізь призму апоптозу та тіол-дисульфідного балансу - Крайдашенко, Олег Вікторович; Тягла, Оксана Сергіївна; Крайдашенко, О. В.; Тяглая, О. С.; Kraidashenko, O. V.; Tyagla, O. S. (My University, 2021)
Метою даного дослідження була оцінка якості життя та респіраторних порушень у пацієнтів із хронічним обструктивним захворюванням легень та гіпертонічною хворобою в контексті дослідження маркерів апоптозу та тіол-дисульфідного балансу. Матеріал та методи. Результати дослідження базуються на даних комплексного обстеження та динамічного спостереження за 121 хворим обох статей у віці від 30 років до 67 років, які були обстежені в період 2016-2018 рр. та перебували на стаціонарному лікуванні в КНП «Запорізька обласна клінічна лікарня» ЗОР. Результати. У хворих на хронічне обструктивне захворювання легень у поєднанні з гіпертонічною хворобою встановлено достовірну елевацію проапоптотичного маркера каспази-7 порівняно з групою хворих на ізольовану гіпертонічну хворобу та групою хворих на хронічне обструктивне захворювання легень (у 3,73 та 2,16 раза, відповідно; р <0,05). Найвищий рівень каспази-9 відзначався у групі хворих із коморбідністю хронічного обструктивного захворювання легень та гіпертонічної хвороби і перевищував аналогічний показник у пацієнтів із гіпертонічною хворобою на 60% та з хронічним обструктивним захворюванням легень на 85,83% (р <0,05). Целью исследования была оценка качества жизни и респираторных нарушений у пациентов с хроническим обструктивным заболеванием легких и гипертонической болезнью в контексте исследования маркеров апоптоза и тиол-дисульфидного баланса. Материал и методы. Результаты исследования базируются на данных комплексного обследования и динамического наблюдения за 121 больным обоих полов в возрасте от 30 до 67 лет, которые были обследованы в период 2016-2018 гг. и находились на стационарном лечении в КНП «Запорожская областная клиническая больница» ЗОС. Результаты. У больных с хроническим обструктивным заболеванием легких в сочетании с гипертонической болезнью установлена достоверная элевация проапоптотического маркера каспазы-7 по сравнению с группой больных с изолированной гипертонической болезнью и группой больных с хроническим обструктивным заболеванием легких (в 3,73 и 2,16 раза, соответственно; р <0,05). Самый высокий уровень каспазы-9 отмечался в группе больных с коморбидностью хронического обструктивного заболевания легких и гипертонической болезнью, и превышал аналогичный показатель у пациентов с гипертонической болезнью на 60% и с хроническим обструктивным заболеванием легких на 85,83% (р <0,05). The purpose of the study was an assessment of the quality of life and respiratory disappearances in patients with chronic obstructive pulmonary disease and essential hypertension in the context of the study of apoptosis markers and a thiol-disulfide balance. Materials and methods. The results of the study are based on the data of a comprehensive examination and dynamic observation of 121 patients of both sexes aged 30 to 67 years, who were examined in the period 2016-2018 and received inpatient treatment at the municipal non-profit enterprise «Zaporizhzhya Regional Clinical Hospital» of Zaporizhzhya regional council. The patients were divided into 3 groups, comparable in age and sex: the main group included 40 patients with chronic obstructive pulmonary disease stage II-III (moderate) in combination with essential hypertension stage II of different cardiovascular risk (mean age 50.81±0.99 years); the 1st comparison group included 48 patients with chronic obstructive pulmonary disease stage II-III (mean age 50.7±1.53 years); the second comparison group consisted of 33 patients with essential hypertension stage II with different cardiovascular risk (mean age 51.68±1.22 years). To determine the reference values of the studied indicators, 20 healthy individuals were examined as a control group. Results and discussion. In patients with chronic obstructive pulmonary disease, in combination with essential hypertension, a reliable element of the pro-apoptotic marker of Caspase-7 was established compared with the group of patients with an isolated essential hypertension and a group of patients with chronic obstructive pulmonary disease (by 3.73 and 2.16 times, respectively; p <0.05). The highest level of Caspase-9 was noted in the group of patients with the comorbidity of the chronic obstructive pulmonary disease and essential hypertension, and exceeded the same indicator in patients with essential hypertension by 60% and chronic obstructive pulmonary disease by 85.83% (p <0.05).
Качество жизни и респираторные нарушения у пациентов с хроническим обструктивным заболеванием легких и гипертонической болезнью: взгляд сквозь призму апоптоза и тиол-дисульфидного баланса
Quality of Life and Respiratory Disorders in Patients with Chronic Obstructive Pulmonary Diseases and Essential Hypertension: Look through the Prism of Apoptosis and Thiol-Disulfide Balance
O. V. Kraidashenko -: 0000-0002-8911-3292; O. S. Tyagla - 0000-0002-2807-6846.
Keywords: хронічне обструктивне захворювання легень; гіпертонічна хвороба; апоптоз; тіол-дисульфідний баланс; якість життя; хроническое обструктивное заболевание легких; гипертоническая болезнь; тиол-дисульфидный баланс; качество жизни; chronic obstructive pulmonary disease; essential hypertension; apoptosis; thiol-disulfide balance; quality of life